2022
DOI: 10.3390/ijerph192416947
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Australians’ Experiences of Cancer Care: A Narrative Literature Review

Abstract: To provide the latest evidence for future research and practice, this study critically reviewed Indigenous peoples’ cancer care experiences in the Australian healthcare system from the patient’s point of view. After searching PubMed, CINAHL and Scopus databases, twenty-three qualitative studies were included in this review. The inductive approach was used for analysing qualitative data on cancer care experience in primary, tertiary and transitional care between systems. Three main themes were found in healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(215 reference statements)
0
3
0
Order By: Relevance
“…Previous reviews have found that cultural competency training for healthcare professionals can improve the health behaviours of their culturally diverse patients [ 103 ]. Cultural competency training, while not the only solution needed, is an important step in helping non-Indigenous healthcare professionals understand the intricacies of the Aboriginal and Torres Strait Islander peoples’ culture and how it can either help or hinder cancer care provision [ 30 , 104 ]. It should be acknowledged that the cultural competency of healthcare professionals is reliant on societal level actors or “owners of the system” as they determine funding and the importance that is placed on delivering the best possible care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have found that cultural competency training for healthcare professionals can improve the health behaviours of their culturally diverse patients [ 103 ]. Cultural competency training, while not the only solution needed, is an important step in helping non-Indigenous healthcare professionals understand the intricacies of the Aboriginal and Torres Strait Islander peoples’ culture and how it can either help or hinder cancer care provision [ 30 , 104 ]. It should be acknowledged that the cultural competency of healthcare professionals is reliant on societal level actors or “owners of the system” as they determine funding and the importance that is placed on delivering the best possible care.…”
Section: Discussionmentioning
confidence: 99%
“…The increased prevalence of, and mortality from cancer among Aboriginal and Torres Strait Islander peoples is largely due to socially driven increased prevalence of cancer risk factors 20. Additional upstream factors that affect Aboriginal and Torres Strait Islander peoples’ cancer experiences include barriers to accessing cancer services such as screening and treatment 21 22…”
Section: Introductionmentioning
confidence: 99%
“… 20 Additional upstream factors that affect Aboriginal and Torres Strait Islander peoples’ cancer experiences include barriers to accessing cancer services such as screening and treatment. 21 22 …”
Section: Introductionmentioning
confidence: 99%